Multiresponsive Luminescence Materials: Richer Color Than Chameleon Materials. Issue 12 (15th April 2020) - Shi, Chen; Hou, Xuebin; Shen, Xiuyu; Zhu, Yanan; Li, Xiaoqiang; Pang, Zengyuan; Ge, Mingqiao; Abolhasani, Milad
Abstract: Developing light‐harvesting materials with tunable emission colors is highly desirable in applications requiring a specific color on‐demand. The modulation in material composition, structures, and polymerization can provide a useful tool for producing a wide range of emission colors. However, controlling the color gamut in a ready‐made material remains a formidable challenge. Here, several germinate‐based phosphors are reported that provide precise dynamic emission color tuning in the visible color range through the optical multiplexing of lanthanides and other ion dopants, such as lead (Pb 2+ ) and manganese (Mn 2+ ). The emission gamut of the developed germinate‐based materials in the full visible color range can be tuned on demand by adjusting the excitation wavelength, thereby allowing dynamic synergistic multicolor, multitemporal, and multimodal integration with ready‐made materials. The multicolored photoluminescence property of the developed phosphors is related to the different interaction modes of dopants in the crystals. Furthermore, the applications of color‐tunable phosphors in multicolor display and anticounterfeiting are demonstrated. These findings provide valuable insights toward developing next‐generation smart luminescent materials and sensors. Abstract : In this study, iridescent chameleon‐like phosphors that can change their emission color under different photostimulation are reported. The as‐prepared phosphors exhibit excitation wavelength‐dependent fluorescence, long‐persistent afterglow (including blue, green, and orange), upconversion emission, and near‐infrared photostimulated luminescence. These findings provide valuable insights toward developing next‐generation smart luminescent materials and sensors.